ABDOLKARIM SOROUSH: REKONSILIASI KEBERAGAMAN DAN TRANSFORMASI AJARAN AGAMA - Al-Razi, Muhammad Fakhruddin; Kamilia, Nur (UIN Sumatera Utara Medan, 2025)
In religious life, there are many differences in characteristics and styles of religious teachings and practices. These differences do not only appear in the context between groups but also between generations. In Islam itself, diversity has existed for a long time until the present. The crucial problem of the many differences is the emergence og claims to absolute truth from each group which often also leads to conflict. To get out of the circle of disputes, this article proposes the views of an Islamic thinker, namely Abdolkarim Soroush, regarding the theory of contraction and expansion. This article includes the results of qualitative research with data sources and documents published from various sources of scientific papers in the from of books and articles and also from other data sources related to this article. The result of this article regarding Soroush’s ideas is that it is necessary to distinguish between religion and religious knowledge in order to achieve effective reconcilation in seeing how one should behave in the presence of many different views, which what we have considered so far is understanding religion, non religion so that there will be potential truth and falsity from each group’s perspective. From this reason, the attitude that needs to be taken is to explore the many different views in order to gain new meanings from religious teachings, not necessarily fight over each other’s claims to the authority of absolute truth.